2021
DOI: 10.3390/ijerph18189646
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Views on the Use of Physical Restraints in Intensive Care: A Qualitative Study

Abstract: Despite the worldwide promotion of a “restraint-free” model of care due to the questionable ethical and legal issues and the many adverse physical and psychosocial effects of physical restraints, their use remains relatively high, especially in the intensive care setting. Therefore, the aim of the present study was to explore the experiences of nurses using physical restraints in the intensive care setting. Semi-structured interviews with 20 nurses working in intensive care units for at least three years, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 21 publications
(58 reference statements)
0
26
0
1
Order By: Relevance
“…Critical care nurses' intention of physical restraint is to ensure patient safety and maintain job security. Some studies reported that patient safety is the primary trigger (Canzan et al, 2021; Cui, Qiu et al, 2021; Dolan & Dolan, 2017; Langley et al, 2011; Perez et al, 2021; Salehi et al, 2020; Shen et al, 2021; Via‐Clavero et al, 2019; Wang et al, 2015; Yang & Li, 2017). Interruption or removal of invasive monitoring and therapeutic devices were identified as a significant threat to patient safety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Critical care nurses' intention of physical restraint is to ensure patient safety and maintain job security. Some studies reported that patient safety is the primary trigger (Canzan et al, 2021; Cui, Qiu et al, 2021; Dolan & Dolan, 2017; Langley et al, 2011; Perez et al, 2021; Salehi et al, 2020; Shen et al, 2021; Via‐Clavero et al, 2019; Wang et al, 2015; Yang & Li, 2017). Interruption or removal of invasive monitoring and therapeutic devices were identified as a significant threat to patient safety.…”
Section: Resultsmentioning
confidence: 99%
“…Communication with patients is the most commonly used alternative, which can reassure patients about what is happening and how they can better manage their fear or pain. (Canzan et al, 2021; Dolan & Dolan, 2017; Langley et al, 2011; Teece et al, 2021). As one nurse described, “For us [nurses] it is essential before arriving to restrain, have faith in the patient, especially if he/she is awake, and so to talk and to stay close to the patient (Canzan et al, 2021) .” Once patients become irritable or uncooperative, it is necessary to assess the reasons for agitation (Canzan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In inpatient settings, nursing staff play crucial roles in the decision-making process as well as in the application of restraint, as they are most intensively involved in patient care [ 7 , 9 , 10 ]. It is well known that the decision-making process for the use of restraint is influenced not only by contextual (e.g., availability of guidelines) and patient-related factors (e.g., aggressive behaviour) but also by the individual conditions of the staff [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the somatic acute care hospital (henceforth referred to as ‘hospital’) setting, little is known about the attitudes of the nursing staff. Some studies have been conducted in the intensive care area (e.g., [ 10 , 21 , 22 , 23 ]); however, these focused more on reasons for the use of restraints (e.g., using the Perception of Restraint Use Questionnaire), on knowledge and application practices (partly using questionnaires designed for the study), or on attitudes assessed only using qualitative methods. Therefore, the aim of the current study is to assess nursing staff’s attitudes in a hospital setting using a standardised questionnaire and to identify their associations with staff characteristics.…”
Section: Introductionmentioning
confidence: 99%